100 let R. U. R. Sborník z konference na Pedagogické fakultě Masarykovy univerzity v Brně, 11. září 2019 - Drozenová, Wendy (Masaryk University Press, 2020)
Title in English: Hundred years of R. U. R.: Post-conference proceeding, Faculty of Education, Masaryk University, 11th September 2019. The publication is a post-conference proceeding marking the 100 years since Karel Čapek's first issuance of the science fiction play R. U. R. and the invention of the term robot by his brother Josef. The individual contributions within the proceeding are the result of an individual research of the conference participants. The published texts analyze the connotations of the term "robot" and reflect the social context of robotics, technology, and artificial intelligence. The reflection of the influence of visions from the work of Karel Čapek is also discussed. The papers possess a diverse character, the proceeding contains a philosophical essay, historical probes, philosophical analyzes and pedagogical applications of Čapek's work and legacy.